2011
DOI: 10.1089/ten.tea.2010.0175
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Derived Matrix Enhances Osteogenic Properties of Hydroxyapatite

Abstract: The study aimed to evaluate osteogenic properties of hydroxyapatite (HA) scaffold combined with extracellular matrix (ECM) derived in vitro from rat primary calvarial osteoblasts or dermal fibroblasts. The cellular viability, and the ECM deposited onto synthetic HA microparticles were assessed by MTT, Glycosaminoglycan, and Hydroxyproline assays as well as immunohistochemistry and scanning electron microscopy after 21 days of culture. The decellularized HA-ECM constructs were implanted in critical-sized calvar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 45 publications
1
76
0
Order By: Relevance
“…17,18 However, in the current study, stem cells were not cultured in osteogenic media prior to surgical transplantation; yet, encapsulated PDLSCs and GMSCs promoted bone regeneration in situ without any premineralization. Additionally, we confirmed that the presence of RGD tripeptide and the small diameter of alginate microspheres are crucial factors for MSC survival and fate determination.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…17,18 However, in the current study, stem cells were not cultured in osteogenic media prior to surgical transplantation; yet, encapsulated PDLSCs and GMSCs promoted bone regeneration in situ without any premineralization. Additionally, we confirmed that the presence of RGD tripeptide and the small diameter of alginate microspheres are crucial factors for MSC survival and fate determination.…”
Section: Discussionmentioning
confidence: 84%
“…15,16 Studies have confirmed that providing a suitable microenvironment for MSC proliferation and differentiation in response to exogenous stimuli and growth factors is a critical step toward clinical applications. [17][18][19][20][21][22][23] Several types of scaffolds have been used to support growth and differentiation of progenitor cells for bone regeneration, including natural polymers (e.g., alginates). 23,24 Alginates are natural heteropolysaccharides that are isolated from brown sea algae.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, eECM displayed efficient engraftment [74] and vascularization [75] and was capable to undergo remodeling onto an immature osteoid tissue [71]. eECM was successfully shown to act as functional/instructive template for the regulation and/or recruitment of osteoprogenitor cells, although it could not ectopically induce frank bone formation in mouse and rat models [71,76].…”
Section: Decellularized Engineered Ecm (Eecm)mentioning
confidence: 99%
“…Such interactions between stem cells and biomaterials have largely been studied by introducing the cells into 2- or 3-dimensional scaffolds, or by encapsulating the cells within hydrogel biomaterials. 3032 Alginate hydrogel has been used extensively as a vehicle for stem cell delivery in tissue regeneration. 31,32 The ability to control the spatial presentation of alginate enables the examination of the effects of alginate hydrogel on stem cell differentiation in a systematic way.…”
Section: Introductionmentioning
confidence: 99%